Adoption of Project Management Methodology and Challenges Faced: A Comparative Analysis between Government IT Sector and IT Organisations in the Corporate Sector in Kerala - Chandrachooodan, Gayathri; R., Dr.Radhika; R., Dr.Ramesh Palappan (Webology, 2021)
Adoption of a Project Management methodology is highly critical in the success of projects in any domain. It is imperative that a matured project management methodology is significant in the successful implementation of projects. Various Project management methodologies such as PMBOK, Waterfall, PRINCE2, Agile, etc. are followed in different domains including IT. Yet challenges remain and very few projects are able to adopt these methodologies for project success. This paper covers a comparative analysis between corporate IT organisations operating in Kerala and IT organisations owned by Government of Kerala. The paper aims to identify the project management methodology, the level of project management practices, the reasons for project failures and the challenges in the adoption of a Project management framework. The study was conducted among 50 employees of four IT organisations in Government sector and 50 employees of Corporate IT sector in the state of Kerala, India. The focus is to understand the differences in project management practices, specific challenges in adoption of Project Management methodology between Government IT sector and Corporate IT organizations in Kerala. This study aims to enhance in the current practices of project management to create more successful projects in IT domain in Government Sector.